SISTEM MONITORING KETERSEDIAAN BAHAN BAKU COR BETON MENGGUNAKAN METODE MARKET BASKET ANALYSIS - Rometdo Muzawi; Tashid Tashid; Mahadir Nasution (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2019)
Cast concrete is very important in building physical buildings, both for the construction of houses, hotels, bridges, apartments and other physical buildings. The concrete cast material is the most chosen by the community in building buildings because it is easily formed according to the needs of construction and has a strong strength and is resistant to high temperatures. "Inventory is a component of material or finished product available in hand, waiting to be used or sold" (Groebner in Baroto, 2002: 52). Monitoring raw material inventory is a management function that is very important because inventory is a very large investment company, both in terms of value and future functions. So from that the company needs to implement planning regarding inventory control which estimates the accuracy between inputs into output and the accuracy of the quantity or volume of raw materials. In the real world there are many companies that have not noticed the importance of managing raw material inventories, this can be found in companies that experience excess raw materials in warehouses, as well as running out of raw materials. Monitoring inventory that is well implemented can trigger the success of a company in the production sector in a timely manner. In manufacturing companies often encountered a delay in the arrival of raw materials according to a predetermined schedule. This can create panic at the company's management if there is a stock out, where on the other hand the company must immediately fulfill the goods orders. Therefore, monitoring the availability of concrete cast materials is very important to support the smooth production and can avoid the vacuum of concrete cast material. If the availability of concrete cast raw materials does not monitor, it will cause difficulties in knowing whether or not there is still a concrete cast material to be produced. On this basis the author makes a monitoring system for the availability of concrete cast raw materials using the Market Basket Analysis method.